Catalyst-Controlled Regioselective Reactions of Carbohydrate Derivatives - Lee, Doris; Taylor, Mark S. (Synthesis, 2012)
The efficient synthesis of oligosaccharides requires methods for regioselective manipulation of hydroxyl groups in monosaccharide derivatives. Catalysis represents a potentially general solution to this problem, and over the past decade, the development of catalyst-controlled methods for regioselective functionalization of carbohydrates has intensified. This Short Review highlights the range of catalysts and catalytic mechanisms that may be exploited to alter the reactivity of hydroxyl groups in carbohydrate substrates. 1 Introduction2 Intrinsic Trends in the Reactivity of Carbohydrate Hydroxyl Groups2.1 Steric Control2.2 Electronic Control3 Enzyme Catalysis4 Phase-Transfer Catalysis5 Lewis Base Catalysis5.1 Peptide-Based Catalysts5.2 Modified DMAP Catalysts5.3 Chiral Amines6 Lewis Acid Catalysis6.1 Tin(IV) Reagents6.2 Transition-Metal Reagents6.3 Lanthanum(III) Reagents6.4 Multistep One-Pot Methods6.5 Organoboron Reagents7 Conclusions and Outlook
Keywords: carbohydrates; Lewis acid catalysis; Lewis base catalysis; protecting groups; regioselectivity